2007
DOI: 10.1186/1471-2458-7-345
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and deficiency of iron, folic acid, and zinc in children younger than 2 years of age who use the health services provided by the Mexican Social Security Institute

Abstract: Background: In Mexico, as in other developing countries, micronutrient deficiencies are common in infants between 6 and 24 months of age and are an important public health problem. The objective of this study was to determine the prevalence of anemia and of iron, folic acid, and zinc deficiencies in Mexican children under 2 years of age who use the health care services provided by the Mexican Institute for Social Security (IMSS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
4
25
2
6
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][18][19][20][21][22][23][24][25][26] The factors contributing to nutritional anemia in children have been extensively studied both in India and other countries. [4][5][6][7][8][9][10][11][18][19][20][21][22][23][24][25][26] To name some of them, are: Poor nutritional intake, low iron bioavailability, low folate and Vitamin B 12 intake, lower age, poverty, less maternal education, increasing family size, less iron intake, bottlefeeding, prolonged breast-feeding without proper weaning, malaria infection, lack of maternal antenatal care, Food insecurity, increasing birth order, less birth interval, low family income, lack of sanitation etc. Age of the child is known to be a significant factor associated with nutritional anemia in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][18][19][20][21][22][23][24][25][26] The factors contributing to nutritional anemia in children have been extensively studied both in India and other countries. [4][5][6][7][8][9][10][11][18][19][20][21][22][23][24][25][26] To name some of them, are: Poor nutritional intake, low iron bioavailability, low folate and Vitamin B 12 intake, lower age, poverty, less maternal education, increasing family size, less iron intake, bottlefeeding, prolonged breast-feeding without proper weaning, malaria infection, lack of maternal antenatal care, Food insecurity, increasing birth order, less birth interval, low family income, lack of sanitation etc. Age of the child is known to be a significant factor associated with nutritional anemia in children.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors from all over the world have shown that younger age is associated with nutritional anemia. [18][19][20][21][22][23][24][25][26][29][30] This has been attributed to the incompleteness of weaning practices, exclusive breast feeding till late age or top feeding with predominantly diluted feeds. All of these studies are prevalence studies on population groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is related to poor nutritional iron intake, low iron bioavailability, and low socioeconomic status [10,11]. Other nutrients such as folate and vitamin B 12 also probably play a role in childhood anemia, and deficiency of these nutrients also may result in anemia [12][13][14]. In this study of 1000 children from a low socioeconomic area of New Delhi, India we measured hemoglobin (Hb) concentrations to assess the prevalence of anemia.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many groups have sought ways to educate vulnerable individuals concerning methods of increasing dietary Fe (Samadpour et al 2004;Haider and Bhutta 2006;Iannotti et al 2006;Mannar 2006). Additionally, ID is associated with homeostatic dysregulation of other metals (e.g., manganese (Mn), copper, zinc) (Pathak et al 2004;Duque et al 2007;Knovich et al 2008). Indeed, it is known that various regions of the brain are especially vulnerable to ID-associated Mn accumulation (Erikson et al 2002(Erikson et al , 2004Brain et al 2006), as well as ID-related zinc dysregulation (Shoham and Youdim 2002).…”
Section: Introductionmentioning
confidence: 99%